The inhibitory effect of moral emotions on malevolent creativity: Exploring the mediation role of emotional valence and prosocial behavior - Fu, Hongyu; Zhang, Zhonglu (Frontiers in Psychology, 2022)
The current study aims to investigate the influence of positive and negative moral emotions (gratitude and guilt) on malevolent creativity, by exploring the potential mediation role of valence and prosocial behavior. Using autobiographical recall, three groups of participants developed gratitude, guilt, or neutral emotion respectively, and then their prosocial behavior and malevolent creativity performance were compared. Results showed that compared with the neutral condition, individuals in the gratitude state experience more positive emotions with less malevolent creative ideas, but the positive valence pathway is a positive effect on malevolent creativity, indicating the promoting effect of positive emotion on creativity. By contrast, individuals in the guilt state experience more negative emotions, which results in less malevolent creativity. Gratitude and guilt promoted prosocial behaviors, which did not mediate the effect of gratitude or guilt on malevolent creativity. In short, the results indicate that the positive and negative moral emotions (gratitude and guilt) inhibit malevolent creativity, which is mediated by valence instead of prosocial behavior.